Arabic Scrabble as a Game-Based Learning Innovation for Vocabulary Mastery in AI-Oriented Arabic Education - Fikriyah, Risti; Ihsan Satrya Azhar (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study investigates the implementation of Arabic Scrabble as a game-based learning innovation for enhancing Arabic vocabulary mastery among seventh-grade students at Darul Ihsan Modern Islamic Boarding School within the framework of AI-oriented Arabic education. The study responds to the continuing challenges of Arabic vocabulary learning, particularly students’ difficulties in memorizing and using vocabulary communicatively in classroom interaction. Using a qualitative phenomenological case study approach, data were collected through non-participant observation, semi-structured interviews, and documentation involving Arabic teacher and seventh-grade students. The findings reveal that the implementation of Arabic Scrabble created a more interactive and student-centered learning environment by increasing learner engagement, collaborative learning, vocabulary retention, and students’ confidence in using Arabic vocabulary. Through activities such as arranging Arabic letters into words, discussing meanings collaboratively, and constructing simple sentences, students became more active and motivated during the learning process. Furthermore, the study indicates that Arabic Scrabble reflects several characteristics associated with AI-oriented Arabic pedagogy, particularly interactive, adaptive, and engagement-based learning experiences. This study contributes to the discourse of game-based Arabic learning by positioning Arabic Scrabble not merely as an educational game, but as a pedagogical innovation that supports learner-centered Arabic education in modern Islamic boarding schools.